Hepatocellular Carcinoma Advances in Diagnosis and Treatment - Teodor Streba, Costin; Constantin Vere, Cristin; Rogoveanu, Ion (IntechOpen, 2018)
Hepatocellular carcinoma (HCC) currently ranks as the third most common cause of death. As the primary malignancy of the liver is directly related to an underlying liver condition, its incidence and profile are expected to change soon. While effective prevention programs and antiviral therapies for hepatitis B and C will lower the incidence of HCC, emerging socioeconomic issues will deliver new at-risk populations. Moreover, diagnostic techniques and protocols have undergone significant advancements. Reliance on contrast enhanced ultrasound has been re-evaluated, imaging methods being considered as sufficient diagnostic tools. Molecular characterization remains desirable, since chemotherapeutic agents still have limited applicability. In light of recent diagnostic advancements and novel therapeutic solutions, it is our belief that a comprehensive update on recent paradigm shifts and interesting upcoming developments is highly needed.